2023
DOI: 10.3389/fnins.2023.1242254
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the role of gut microbiota in Alzheimer’s pathogenesis and envisioning future therapeutic avenues

Junyi Liang,
Bin Liu,
Xiaohong Dong
et al.

Abstract: Alzheimer’s disease (AD) emerges as a perturbing neurodegenerative malady, with a profound comprehension of its underlying pathogenic mechanisms continuing to evade our intellectual grasp. Within the intricate tapestry of human health and affliction, the enteric microbial consortium, ensconced within the milieu of the human gastrointestinal tract, assumes a role of cardinal significance. Recent epochs have borne witness to investigations that posit marked divergences in the composition of the gut microbiota be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 207 publications
0
8
0
Order By: Relevance
“…This summary underscores the critical importance and urgency of using probiotics and advancing research related to cognitive aging. Ongoing studies aim to deepen our understanding of the interactions within the microbiome–gut–brain axis, particularly exploring mechanisms between the gastrointestinal tract and the nervous system [ 122 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Future research should focus on more precise analyses and explorations of the composition of gut microbiota, identifying which strains are dominantly associated with conditions such as anxiety, depression, Parkinson’s disease, and other psychiatric and cognitive disorders, including Alzheimer’s disease [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ].…”
Section: Discussionmentioning
confidence: 99%
“…This summary underscores the critical importance and urgency of using probiotics and advancing research related to cognitive aging. Ongoing studies aim to deepen our understanding of the interactions within the microbiome–gut–brain axis, particularly exploring mechanisms between the gastrointestinal tract and the nervous system [ 122 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Future research should focus on more precise analyses and explorations of the composition of gut microbiota, identifying which strains are dominantly associated with conditions such as anxiety, depression, Parkinson’s disease, and other psychiatric and cognitive disorders, including Alzheimer’s disease [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is research that suggests that DGBI might be a risk factor or predisposing factor for the development of IBD. This intriguing connection underscores the intricate nature of the interplay between the DGBI and the development of chronic inflammatory conditions in IBD, mainly dysbiosis related to chronic inflammation [ 7 , 11 - 14 ]. A potential theory is that the symptoms that relate to DGBI could represent chronic subclinical inflammation related to IBD that would later manifest in a different phenotype that would be more in keeping with a clinical picture of IBD [ 8 , 15 , 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…DGBI is very common worldwide, with a prevalence of 40%, being more common in women than men, and they account for 30% of gastroenterology outpatient consultations. This condition is often accompanied by other related chronic health conditions such as fibromyalgia, metabolic disorders, chronic fatigue syndromes, and mental health conditions such as depression and anxiety [ 11 , 14 ]. It is also seen in other organic chronic health issues such as chronic kidney disease and heart failure, as this can come with psychological issues that could lead to DGBI.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, the authors found a decrease in fungal richness in the feces of AD mice, which may be related to metabolic changes in AD ( D’Argenio et al, 2022 ). Liang et al (2023) transplanted Paenalcaligenes hominis isolated from the feces of elderly humans and mice into young mice and found a decline in cognitive function in the mice.…”
Section: Biomarkers Of Alzheimer’s Diseasementioning
confidence: 99%